Bleaching Of Fatty Acids With Obtained Adsorbents - D.S., Salihanova; D.T., Ruzmetova; I.D., Eshmetov; D.S., Sagdullaeva; M.A., Mamajonova; M.A., Ismoilova; D.A., Azimova (The journal of contemporary issues in business and government, 2021)
This article presents the results of the adsorptive purification of fatty acids from dyes by the obtained clay adsorbents. It was determined that phospholipids, which are classified as nonionic surfactants, exhibit the highest sorption activity. On the contrary, gossypol and its derivatives show the least. An intermediate position is occupied by palmitic and linoleic acids, which are found in large quantities in cotton soap stock. It was found that the sorption activity of phospholipids with an increase in the temperature of the process of purification of fatty acids in cotton soap stock are arranged in the following order of decreasing: phosphatidylcholines>phosphatidylserines>phosphatidylethanolamines>phosphatidic acids, etc.